2016
DOI: 10.3892/or.2016.5260
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic paclitaxel-octreotide conjugate reverses the resistance of paclitaxel in A2780/Taxol ovarian cancer cell line

Abstract: The high mortality of ovarian cancer is partly due to the frequent resistance of ovarian cancer to current chemotherapy agents such as paclitaxel and platinum. Somatostatin analogue (SSTA) has been shown to inhibit the proliferation of some tumors through binding to somatostatin receptor (SSTR) and activation of Ras-, Rapl- and B-Raf-dependent extracellular signal-regulated kinase 2 (Erk2). It was reported that paclitaxel-octreotide conjugate (POC) exhibited enhanced tumor growth inhibition with reduced toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Previous reports have found that STAT3 and NF-kB signal pathways involved in growth and invasion of ovarian cancer cells (30)(31)(32)(33). Evidence has shown that paclitaxel can be regarded as an efficient therapy for human ovarian cancer and the therapy of paclitaxel combined with other drugs provides a potential approach to overcome the resistance of ovarian cancer (34)(35)(36). Pashaei-Asl et al (17) reported that combination of the chemotherapy drugs silibinin and paclitaxel can be more efficient in treatment of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have found that STAT3 and NF-kB signal pathways involved in growth and invasion of ovarian cancer cells (30)(31)(32)(33). Evidence has shown that paclitaxel can be regarded as an efficient therapy for human ovarian cancer and the therapy of paclitaxel combined with other drugs provides a potential approach to overcome the resistance of ovarian cancer (34)(35)(36). Pashaei-Asl et al (17) reported that combination of the chemotherapy drugs silibinin and paclitaxel can be more efficient in treatment of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We preliminary synthesized octreotide-paclitaxel conjugate (POC, patent No. : ZL 2013 1 2013 X), and experimental studies of the resistance to A2780/Taxol cells and tumor-burdened nude mice confirmed that the octreotide-paclitaxel conjugate has a highly property of targeting [ 11 ]. Tumor-burdened nude mice experiments in vivo observed that octreotide-paclitaxel conjugate effectively inhibited ovarian cancer resistance cell A2780/Taxol proliferation, increased the sensitivity of the A2780/Taxol cells to paclitaxel (PTX), and octreotide-paclitaxel conjugate showed low toxicity to normal organs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five subtypes of somatostatin receptors SSTRs, namely SSTR1-5, and SSTR2 expression are seen in most of these tumors (Shahbaz et al., 2015; Kharmate et al., 2013). Artificially synthesized somatostatin analog (SSTA) such as octreotide (OCT) could specifically bind to SSTR2 to achieve the purpose of targeting tumor cells with SSTR2 expression (Ju et al., 2018; Shen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%